Environmental Resource Conflicts and Food Insecurity in Rural Southeast Nigeria: Implications for Humanitarian and Sustainable Development Policies - Okafor, Samuel; Ogbochie, Andrew; Ugwu, Chukwuka; Oranu, Chizoba; Amadi, Gloria; Ugwuanyi, Chigozie; Modesta, Okolo (Journal of Agriculture and Environment for International Development (JAEID), 2025)
Environmental resource crises involving farmers and herdsmen in developing nations can affect the realisation of the United Nations 2030 Sustainable Development Goals’(SDGs) targets, such as elimination of poverty, elimination of hunger and food insecurity, peace and safety of the human settlements, as well as sustainable production and consumption. This study examined this situation among indigenous farmers and migrating herdsmen in southeast Nigeria. The study aimed to examine the relationship between environmental resource access crises and food insecurity indicators in southeast Nigeria, as well as investigate the social indicators of climate change and environmental resource access crises and the predictors of resource access crises among the farmers and herders. This study involved 1658 respondents and was guided by the Resource Access Theory (RAT) (Ribot & Peluso, 2003). The study applied a survey research design with multistage and probability sampling techniques. Data were collected with a questionnaire instrument developed using FAO, IFAD, UNICEF, WFP and WHO’s (2019) mild, moderate and severe food insecurity scale, and Coleman et al.’s (2013) Household Food Security Survey Module [HFSSM]. Percentage analysis, Spearman’s rho Correlation and multiple linear regression statistics were utilised in analysing the collected data. The analysis revealed a strong positive correlation between environmental resource-access crises and food utilization rho (1658) = .329 P =.01, a decrease in food stability rho (1658) = .308 P =.01, a decrease in food access rho (1658) = .234 P =.01, a decrease in food availability rho (1658) = .526 P =.01, and a decrease in food production rho (1658) = .307 P =.01. There is also a positive correlation between climate change and environmental resource-access crises in the region rho (1658) = .388 P =.01, while environmental resource-access crises are predicted by education, religion, climate change, etc (** p<.01, *** p<.000, R2= 72.9).One implication of these findings is that the control of environmental resource-access crises and climate change will eventually reduce the affected dimensions of food insecurity in the region and beyond. Based on these findings, it is recommended that agricultural policies and emerging food security crises be harmonized to create a synergy for proactive intervention. There should be a synergy between agricultural and security policies to address the issue of migration, which is affecting different regions and has enormous implications for food security.